2019
DOI: 10.1021/acs.jpca.8b11321
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Chemical Modulation and Unidirectional Coupling in Two Oscillatory Chemical Systems

Abstract: Controlling and coupling of out-of-equilibrium reaction networks have great importance in chemistry and biology. We provide an example for the ideal master–slave coupling between two pH oscillators (the sulfite–bromate and the hydrogen peroxide–sulfite pH oscillators operated in continuous-flow stirred tank reactors). The coupling between the reactors was realized by transport of carbon dioxide through a silicon membrane, which is a common chemical species in both systems. We showed that by using this strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In recent years, pH feedback systems have garnered increasing interest and have been extensively utilized for the development of adaptive materials thanks to their remarkable properties of autonomous dynamics and pH self-regulation in time domain. [132][133][134] In general, classical pH-responsive systems require external triggers to induce a change in pH so that the materials undergo a unidirectional transition between thermodynamically stable states and revert to original resting state through addition of counter triggers. Unlike classical pHresponsive systems that passively respond to external triggers, dynamic systems with pH feedback-driven features introduce a new paradigm for the development of autonomous adaptive materials.…”
Section: Ph Feedback Loopmentioning
confidence: 99%
“…In recent years, pH feedback systems have garnered increasing interest and have been extensively utilized for the development of adaptive materials thanks to their remarkable properties of autonomous dynamics and pH self-regulation in time domain. [132][133][134] In general, classical pH-responsive systems require external triggers to induce a change in pH so that the materials undergo a unidirectional transition between thermodynamically stable states and revert to original resting state through addition of counter triggers. Unlike classical pHresponsive systems that passively respond to external triggers, dynamic systems with pH feedback-driven features introduce a new paradigm for the development of autonomous adaptive materials.…”
Section: Ph Feedback Loopmentioning
confidence: 99%
“…A similar strategy was used to control the regular and chaotic oscillation regimes in the sulfite−hydrogen peroxide pH oscillatory system. 29 The forced oscillations were realized by the selective transport of carbon dioxide generated periodically in the pH oscillatorfrom the pH oscillator to the solution of the dye that changed periodically the pH in the non-oscillatory subsystem (solution of MR). The periodic change in the transport of carbon dioxide through the silicone membrane affected the pH of the MR solution through carbon dioxide−hydrogen carbonate−carbonate equilibria.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we propose a novel coupling strategy to drive the oscillation of an originally non-oscillatory chemical species, namely, a pH-sensitive dye (methyl red, MR) in a two-compartment system by separating the pH oscillator and the solution of the pH-sensitive chemical species using a silicone membrane. A similar strategy was used to control the regular and chaotic oscillation regimes in the sulfite–hydrogen peroxide pH oscillatory system . The forced oscillations were realized by the selective transport of carbon dioxidegenerated periodically in the pH oscillatorfrom the pH oscillator to the solution of the dye that changed periodically the pH in the non-oscillatory subsystem (solution of MR).…”
Section: Introductionmentioning
confidence: 99%
“…Holló and Lagzi have recently shown that unidirectional coupling can be achieved between two oscillatory systems separated by a silicon membrane 12 where the diffusion of carbon dioxide from one unit to the other is the driving force controlling the system dynamics. Unidirectional inhibitory communication between four almost identical BZ oscillators in continuously stirred tank reactors has yielded new stable modes besides the in-phase and anti-phase, and the existence of bistability has been observed both experimentally and theoretically.…”
mentioning
confidence: 99%